Chlorophyll-a Distribution in Relation to Yellowfin Tuna Catches in Morotai Island Seas - Tangke, Umar; Laitupa, Ibnu W. (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research was conducted in November 2023 - January 2024 in Pualu Morotai Waters with the aim of analyzing the relationship between chlorophyll-a concentration and madidihang fish catch. The use of experimental fishing methods is expected to provide an overview of the relationship between chlorophyll-a concentrations and madidihang fish catches. The results showed that the variability of chlorophyll-a concentrations during the study ranged from 0.18 - 0.39 mg/m3 and had a very strong relationship with mackerel catches of 0.819, with a detemination coefficient (r2) value of 0.6709 and these results were supported by predictions using GAM, where potential mackerel fishing areas in West Halmaheran waters were at chlorophyll-a concentration values of around 0.2 - 0.4 mg/m3